Embryo Implantation and Placental Development - Campagnolo, Luisa (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
This book aims to provide novel insights into the mechanisms of embryo implantation and placental development, as well as at present an overview of the current knowledge on the different signaling pathways regulating the early steps of implantation and placentation, and on the pathological alterations which may impair the establishment of a physiological pregnancy.